An unusual method of forensic human identification: use of selfie photographs. (June 2016) - Miranda, Geraldo Elias; Freitas, Sílvia Guzella de; Maia, Luiza Valéria de Abreu; Melani, Rodolfo Francisco Haltenhoff
Highlights: Owing to advancements in technology and social networks, the selfie photograph has become common. Selfie photographs can be used for human identification. The smile line, superimposition, and IC techniques were used. The selfie can be used as an alternative identification method when no traditional methods of comparison are available. Abstract: As with other methods of identification, in forensic odontology, antemortem data are compared with postmortem findings. In the absence of dental documentation, photographs of the smile play an important role in this comparison. As yet, there are no reports of the use of the selfie photograph for identification purposes. Owing to advancements in technology, electronic devices, and social networks, this type of photograph has become increasingly common. This paper describes a case in which selfie photographs were used to identify a carbonized body, by using the smile line and image superimposition. This low-cost, rapid, and easy to analyze technique provides highly reliable results. Nevertheless, there are disadvantages, such as the limited number of teeth that are visible in a photograph, low image quality, possibility of morphological changes in the teeth after the antemortem image was taken, and difficulty of making comparisons depending on the orientation of the photo. In forensic odontology, new methods of identification must be sought to accompany technological evolution, particularly when no traditional methods of comparison, such as clinical record charts or radiographs, are available.